Intellwheels - a development platform for intelligent wheelchairs for disabled people - Rodrigo A. M. Braga (2008)
Many people with disabilities find it difficult or even impossible to use traditional powered wheelchairs independently by manually controlling the devices. Intelligent wheelchairs are a very good solution to assist severely handicapped people who are unable to operate classical electrical wheelchair by themselves in their daily activities. This paper describes a development platform for intelligent wheelchairs called IntellWheels. The intelligent system developed may be added to commercial powered wheelchairs with minimal modifications in a very straightforward manner. The paper describes the concept and design of the platform and also the intelligent wheelchair prototype developed to validate the approach. Preliminary results concerning automatic movement of the IntellWheels prototype are also presented.